Empowerment Of The Crafters Of Traditional Ceramic Through Development Of Design Based Local Wisdom - Wahida, Adam; Noviani, Leny (2016)

(untitled)
This research aims to empower traditional ceramic crafters in Melikan Village the district of Klaten in Central Java through the form design development, ornaments, and plastic mold technique, so that the resulting ceramic products are able to compete with modern products. This research uses methodology of research development, which includes three main components: 1) model of development, 2) procedure of development, 3) product test. The steps are: 1) collecting information and identify problems of crafters, 2) identify the skills crafters, formulating development goals, determining the order of development, and limited test, 3) developing the design of a product, including: forms, ornaments, and technique of forming, 4) field testing and data analysis, 5) revise the design of the product based on the suggestions of the results of the field test. This research has been generates the shapes of ceramic products are more varied.